Biochar Productive Technologies, Properties and Applications - Bartoli, Mattia; Giorcelli, Mauro; Tagliaferro, Alberto (IntechOpen, 2023)
Biochar is the carbonaceous residue produced from the pyrolytic conversion of biomass. It is generally used for agricultural applications as a soil amendment but has far wider potential. This book presents the use of biochar as a platform for the development of new intriguing solutions in several cutting-edge fields. The book is a useful reference volume for any reader with a strong scientific and technological background, ranging from scientific advisors in private companies to academic researchers promoting the spread of knowledge about biochar to anyone not already working with it.